Estimation of aggregate claim risk model on insurance for damage to buildings due to flooding of the citarum river in Bandung Indonesia - Mustafa, Mamat; Sidi, P.; Santoso, A; Subiyanto, .; Bon, A.T. (2019)
Claim risk for flood insurance is a payment made by an insurance company to policyholders. Actuaries in insurance companies must be able to measure and control the risk of claims, so there will be no loss to insurance companies. In this paper, an estimation of the risk model of aggregate claim risk on damage loss insurance due to flooding of the Citarum river in Bandung Indonesia. Estimates are made on the claim frequency model, and the model for the amount of the claim. Using the claim frequency model estimator, and the claim amount model estimator, then used to estimate the risk of aggregate claims. The results of the analysis show that the claim frequency follows the Poisson distribution model, and the amount of the claim follows the normal distribution model. So that, based on the claim frequency estimator and the claim amount estimator can be used to measure the risk of claims on insurance losses caused by flooding of the Citarum river